(untitled) (The Pakistan Development Review, 1995)
Before her death in 1992, Professor Krishna Bharadwaj had reached the prime of her intellectual growth so that her mature thought on classical political economy and her ideas on development paradigms had begun to coalesce into a single whole. As the title of the book under review implies, this work of the late Indian economist comprises a study of the general problems of economic growth, accumulation, exchange, distribution, and development based on the theory of surplus, including its generation, appropriation, and distribution in society. The author applies classical theory to the complex development process in the developing economies, and to the specific problems of the Indian economy in the industrial, agricultural, and commercial sectors.